Moisture content and fatty acid composition of five tropical fruits - Goes, Maria Edna P. L.; Martins, Carlos Brunet; Teles, Francisco F. Feitosa; Matos, Francisco J. A.; Guedes, Zuleica B. L.; Oria, Humberto Ferreira (Revista Ceres, 2015)
.